2000
DOI: 10.1215/03616878-25-4-653
|View full text |Cite
|
Sign up to set email alerts
|

Systemwide Effects of Medicaid Retrospective Drug Utilization Review Programs

Abstract: Aggregate pooled cross-sectional and time-series annual state data for 1985 to 1992 were used to estimate the systemwide effects of retrospective drug utilization review programs (Retro-DUR) on Medicaid drug and nondrug outcomes. The results provide evidence that these programs produce significant cost savings in the drug budget without spillover effects (positive or negative) in other nondrug budgets within the Medicaid system. We also examine the influence of restricted formularies in this post-Retro-DUR era… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The Annals of Pharmacotherapy ■ 2003 June, Volume 37 ■ 791 www.theannals.com Both qualitative and quantitative studies on the effect of formularies, including effect on changes in prescribing patterns and patient health outcomes, are needed. [26][27][28][29] Future work would include examining the concurrent prescribing of both a topical corticosteroid and topical antifungal/antibiotic. The reason for the increase of the potent topical corticosteroids needs to be further examined.…”
Section: Research Reportsmentioning
confidence: 99%
“…The Annals of Pharmacotherapy ■ 2003 June, Volume 37 ■ 791 www.theannals.com Both qualitative and quantitative studies on the effect of formularies, including effect on changes in prescribing patterns and patient health outcomes, are needed. [26][27][28][29] Future work would include examining the concurrent prescribing of both a topical corticosteroid and topical antifungal/antibiotic. The reason for the increase of the potent topical corticosteroids needs to be further examined.…”
Section: Research Reportsmentioning
confidence: 99%
“…Their findings indicated a strong substitute relationship between prescription drugs and physician and inpatient mental health services. Their updated results examining pharmaceutical drug cost‐containment policies on physician and inpatient services in the Medicaid program (Moore, Gutermuth, & Pracht, 2000) supported earlier findings.…”
Section: Theoretical Frameworkmentioning
confidence: 54%
“…Using aggregated state Medicaid data, Moore et al (2000) found no significant differences in prescriptions per recipient, the number of drug recipients, or average prescription cost between states with or without a retrospective DUR between 1985 and 1992. 56 However, drug expenditures per recipient and total drug expenditures were 4.9% and 6.5% lower, respectively, in states with DUR programs compared with states without DUR programs.…”
Section: Medication Therapy Management: Summary Of the Literaturementioning
confidence: 85%
“…56 However, drug expenditures per recipient and total drug expenditures were 4.9% and 6.5% lower, respectively, in states with DUR programs compared with states without DUR programs. The authors also report no significant spillover effects on nonpharmaceutical expenditures.…”
Section: Medication Therapy Management: Summary Of the Literaturementioning
confidence: 91%